Determinant Factors Influencing the Quality of Financial Reporting Local Government in Indonesia - Tambingon, Henny N.; Yadiati, Winwin; Kewo, Ccecilia Lelly (International Journal of Economics and Financial Issues, 2018)
The purpose of this study to determine factors influencing the quality of financial reporting local government in Indonesia. The factor studied consist of commitment apparatus, role of internal audit, and accounting information system. The sample is picked up randomly by a random sample technique. The data collected is then tested for its validity and reliability so that the data is valid to be processed. The unit of analysis in this study is 66 unit tool of regency/city Indonesian local government . Hypothesis to be tested by a statistical t test: Ho is rejected if tcount > tcritical, Î± = 0.05 level. The results showed that the commitment apparatus, role of internal audit have a significant effect on the quality of accounting information systems. Furthermore it was found that the quality of accounting information system has implications for the quality of financial reporting. Keywords : apparatus commitment, role of internal audit, Quality of accounting information system, financial reporting JEL Classifications : M41, H70, G38